2015
DOI: 10.1002/2014ja020554
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fluctuations of the whistler‐cyclotron and firehose instabilities in a Maxwellian and Tsallis‐kappa‐like plasma

Abstract: Observed electron velocity distributions in the Earth's magnetosphere and the solar wind exhibit a variety of nonthermal features which deviate from thermal equilibrium, for example, in the form of temperature anisotropies, suprathermal tail extensions, and field-aligned beams. The state close to thermal equilibrium and its departure from it provides a source for spontaneous emissions of electromagnetic fluctuations, such as the whistler. Here we present a comparative analysis of the electron whistler-cyclotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
72
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 42 publications
4
72
0
Order By: Relevance
“…Indeed, the Tsallis formalism, which appeared as consequence of using nonadditive entropies, has the distribution function as the main element of the theory (Milovanov & Zelenyi, 2000;Tsallis, 1988Tsallis, , 2009. They have been successfully used, both observationally and theoretically (e.g., Navarro et al, 2015;Pierrard & Meyer-Vernet, 2017;Viñas et al, 2015;Yoon & Livadiotis, 2017), to describe particle distribution functions for velocity or energy (PEDF) 10.1029/2018GL078631 in a number of plasma environments, from the Earth's and other planets magnetospheres (Benson et al, 2013;Kirpichev et al, 2017;Viñas et al, 2005) to solar radio bursts (Cairns et al, 2017). They behave similar to the Maxwellian case for low and central energies but include a power law regime that operates toward higher energies, with a slope determined by the index.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the Tsallis formalism, which appeared as consequence of using nonadditive entropies, has the distribution function as the main element of the theory (Milovanov & Zelenyi, 2000;Tsallis, 1988Tsallis, , 2009. They have been successfully used, both observationally and theoretically (e.g., Navarro et al, 2015;Pierrard & Meyer-Vernet, 2017;Viñas et al, 2015;Yoon & Livadiotis, 2017), to describe particle distribution functions for velocity or energy (PEDF) 10.1029/2018GL078631 in a number of plasma environments, from the Earth's and other planets magnetospheres (Benson et al, 2013;Kirpichev et al, 2017;Viñas et al, 2005) to solar radio bursts (Cairns et al, 2017). They behave similar to the Maxwellian case for low and central energies but include a power law regime that operates toward higher energies, with a slope determined by the index.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmas in nonequilibrium steady states sometimes follow non-Maxwellian velocity distributions, one of the most common known as Kappa distributions [1][2][3]. Properties of Kappa-distributed plasmas have been extensively studied [4][5][6][7], however their origin is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…The higher occurrence rate of chorus waves at dayside was suggested to be caused by the more homogeneous magnetic field, which lowers the threshold of the free energy drive to excite chorus (Spasojevic and Inan, 2010;Keika et al, 20 2012; Katoh and Omura, 2013;Tao et al, 2014b). Note that this threshold condition is different from that for broadband whistler mode waves (Gary, 1993;Gary and Wang, 1996;Viñas et al, 2015), since the generation of broadband whistler waves should be describable using quasilinear theory (Ossakow et al, 1972;Tao et al, 2017c). Recently, using Van Allen Probes wave observations, Li et al (2016) reported that chorus wave normal angle exhibits a bi-modal distribution, with one peak near the quasi-parallel direction and the other peak near the resonance cone.…”
mentioning
confidence: 98%